The impact of electronic banking service on improving the quality of services in banks: Case study of public and private agencies in the City of Tlemcen - Belgaid, Mohammed Djawad; Qwider, Larbi; Belkacem, Zahia (The International tax journal, 2026)
This study aims to find out the impact of electronic banking services on improving the quality of services in banks through some public and private agencies operating in the city of Tlemcen. The study consists of using a questionnaire directed to a sample of 230 customers of those agencies. The results of the study revealed that the quality of banking service is significantly affected by the level of electronic banking services provided and this according to the various dimensions of quality, and there is a statistically significant impact of the application of electronic banking services in improving the quality of banking services.